Intraoperative Contrast‐Enhanced Ultrasound Imaging of Femoral Head Perfusion in Developmental Dysplasia of the Hip: A Feasibility Study. (23rd July 2019) - Back, Susan J.; Chauvin, Nancy A.; Ntoulia, Aikaterini; Ho‐Fung, Victor M.; Calle Toro, Juan S.; Sridharan, Anush; Morgan, Trudy A.; Kozak, Brandi; Darge, Kassa; Sankar, Wudbhav N.
Abstract : Objectives: Developmental dysplasia of the hip (DDH) is one of the most common developmental deformities of the lower extremity. Although many children are successfully treated with a brace or harness, some require intraoperative closed or open reduction and spica casting. Surgical reduction is largely successful to relocate the hip; however, iatrogenic avascular necrosis is a major source of morbidity. Recent research showed that postoperative gadolinium‐enhanced magnetic resonance imaging (MRI) can depict hip perfusion, which may predict a future incidence of avascular necrosis. As contrast‐enhanced ultrasound (CEUS) assesses blood flow in real time, it may be an effective intraoperative alternative to evaluate femoral head perfusion. Here we describe our initial experience regarding the feasibility of intraoperative CEUS of the hip for the assessment of femoral head perfusion before and after DDH reduction. Methods: This single‐institution retrospective Institutional Review Board–approved study with a waiver of informed consent evaluated intraoperative hip CEUS in children with DDH compared to postoperative contrast‐enhanced MRI. Pediatric radiologists, blinded to prior imaging findings and outcomes, reviewed both CEUS and MRI examinations separately and some time from the initial examination both independently and in consensus. Results: Seventeen patients had 20 intraoperative CEUS examinations. Twelve of 17 (70.6%) had prereduction hip CEUS, postreduction hip CEUS, and postreduction gadolinium‐enhanced MRI. Seven of 12 (58.3%) were evaluable retrospectively. All CEUS studies showed blood flow in the femoral epiphysis before and after reduction, and all MRI studies showed femoral head enhancement after reduction. The CEUS and MRI for all 7 patients also showed physeal blood flow. Conclusions: Contrast‐enhanced ultrasound is a feasible intraoperative tool for assessing adequate blood flow after hip reduction surgery in DDH.